A community builds a "bridge": an example of community-led adaptation to sea-level rise in East Kwaio, Solomon Islands. (2nd January 2019) - Asugeni, Rowena; Redman-MacLaren, Michelle; Asugeni, James; Esau, Tommy; Timothy, Frank; Massey, Peter; MacLaren, David
Abstract : Sea-level rise is negatively impacting many Pacific Islands Countries and Territories. In Solomon Islands, sea-level rise is particularly acute due to current movements, the geography of low-lying islands, and the physical structure and locations of villages on the islands. In East Kwaio, Solomon Islands a community-based response to rising sea-levels has meant that men and women from two villages have worked together to independently fund and build a raised walkway, and build seawalls in areas that are regularly inundated. This article describes community-based action, including the processes involved in building the walkway ("bridge") and seawalls, and reports a community discussion with women about the impact of sea-level rise. Changes resulting from the bridge and seawalls, along with recommendations for future action, are reported. Local responses to local concerns underpin this community-based adaptation to sea-level rise in Solomon Islands.